Motivational Factors in Relation to Teachers’ Performance - Sala, Mavic (IJRDO - Journal of Social Science and Humanities Research, 2020)
This study aimed to determine the motivational factors that influence teachers’ job performance. The data pertain to the motivational factors that influence teachers’ motivation which in turn affects their performance. These factors are categorized as existence needs, relatedness needs, and growth needs. The respondents of the study are the teachers of Bacong District, Division of Negros Oriental during the school year 2016 – 2017. The study utilized the descriptive-correlational method of research in the sense that it attempted to determine the motivational factors and their relationship to teachers’ job performance. The study made use of a researcher-made questionnaire that determined the extent to which the motivational factors influence teachers’ performance. The statistical tools used for the treatment of data are Frequency Distribution and Percentage, weighted mean and Pearson Product-Moment Correlation Coefficient. The following are the salient finding of the study. Majority of the teachers in Bacong District are female, on their prime of life, have advanced professionally, occupy Teacher 2 plantilla position, and with considerable years of teaching experience.Teachers’ performance based on the RPMS is “Very Satisfactory”. Teachers are “Very Highly Motivated” by the motivational factors relative to existence needs, relatedness needs and growth needs. The extent to which teachers are motivated by the motivational factors is significantly related to their job performance. Teachers’ profile in terms of sex, educational qualification and teaching experience is significantly related to their job performance based on the RPMS, however, in relation to the extent to which teachers are motivated by the motivational factors, teachers’ profile was found to be insignificant. In general, it was concluded that the higher is teachers’ motivation, the better is their job performance.